Design and development of thermoelectric powered wireless sensor network using soft start approach - Chen, Wei Ping (2021)
Wireless Sensor Networks (WSNs) mainly comprise of a large number of spatially distributed low-power autonomous nodes (SNs) equipped with sensors to cooperatively monitor the environmental conditions. The limited battery lifespan that is being used to operate a sensor node is the major bottleneck that restricts the extension of WSN application. The motivation of this research project s using Thermoelectric Generator (TEG) to harvest the heat energy and convert the heat energy into electrical energy for powering a sensor node. However, the energy harvested by the TEG is too small and insufficient to power up the sensor node as it is relatively power hungry. In addition, there is a power mismatch between the supply energy produced by the TEG and the energy needed by the node to carry out the required tasks. Therefore, the objective of this research project is to develop a low power management system in enabling TEG powered wireless sensor nodes to be operated smoothly. In the experiment, a TEG was sandwiched between a heating element and a heat sink in order to produce a temperature gradient between the TEG with a range between 5°C and 30°C, Then, two power management systems using two different integrated circuits of LTC3108 and MAX757 respectively were compared. Moreover, two soft start circuits based on TC54 and LM741 respectively were designed and compared in terms of sensitivity and charging time, discharging time during the operation a sensor node. These two circuits were implemented in between the capacitor storage and the sensor node. The result proved that the output voltage of TEG is boosted up using LTC3108 and MAX757 t0 3.326V and 3.382V respectively and the maximum power output of TEG is around 29.48mW. Besides, it s also shown that the capacitor voltage (Vcs) for the proposed soft start circuit can be increased up 10 3.3V with a charging time around 20s. It is also act to isolate the capacitor storage with sensor node during the charging process and activation of the sensor node. The charging time for the capacitor storage is 0.2s and the discharging time is about 4s. During the discharging time, the node is in sleep mode. This allows the power management circuit to accumulate enough of power for the next active period. The sensor node based on CC2650 consumed 22.28mW during the data transmission, while consumed 0.11mW during the sleep ‘mode, Thus, it shows that the automatic power management for a sensor node is achicvable with soft-start system which overcomes the start-up problem every time a storage capacitor has been completely discharged.